How an agreement with restriction of unhealthy food marketing and sodium taxation influenced high fat, salt or sugar (HFSS) food consumption - Nongnuch Jindarattanaporn; Sirinya Phulkerd; Aphichat Chamratrithirong; Rossarin Soottipong Gray; Umaporn Pattaravanich; Nutnicha Loyfah; Sasinee Thapsuwan; Natjera Thongcharoenchupong (BMC Public Health, 2024)
Abstract Background Food taxation and food marketing policy are very cost-effectiveness to improve healthy diets among children. The objective of this study was to investigate the socio-demographic characteristics of Thais and attitude towards on policy unhealthy food marketing restriction and sodium taxation which influence high fat, sodium, and sugar (FHSS) food eating. Methods The data were obtained from the 2021 Health Behavior of Population Survey, four-stage sampling method of the Thai people, aged 15 years and above, using a offline survey application-assisted face-to-face interview. Logistic Regression were used to analyze the explanatory variables on agreement and HFSS food intake. Results Almost half (48.4%) of samples disagreed with sodium taxation, and 42.7% of the samples disagreed with food marketing restriction. Most (99.6%) of Thai respondents consumed HFSS food, including sugar sweetened beverages (SSB). Gender, age, education, income, BMI, and health status were associated with agreement with food marketing restriction policy and sodium taxation policy. There is no association between agreement with policy on sodium taxation and food marketing and HFSS food consumption. Conclusion Nearly half of Thais indicated that they disagreed with policy on food marketing restriction and sodium taxation. Therefore, understanding and awareness of the two policies among Thais should be further investigated in order to develop better policy communication for increased public understanding and engagement.